The United Nations’ Approach towards Global Peace and Security: Understanding the Challenging Issues - Owuamanam, Chukwuma Moses; Nwagbo, Samuel N. C. (Social Science Research, 2024)
The United Nations was created after second world war in 1945 to facilitate and oversee global peace. Since then, it has intervened in several war and conflict situations in different countries of the world to maintain peace. Several approaches have been devised to achieve this. However, it is being faced with lots of challenges that limit the efficacy of its functions in maintaining international peace and security. Imperatively, this paper examined issues jeopardizing the efficacy of the United Nations towards global peace and security. Data gathering was through secondary sources like articles, journals, and textbooks. Realist theory by Hans J. Morgenthau served as a theoretical guide for explanation. The study unveiled that some of the issues affecting the UN approaches towards global peace and security are; the United Nations’ lack of courage in addressing effectively matters involving the big 5 permanent members, unfulfilled actions of the United Nations Security Council in areas where the interest of the Super-Powers are not at stake, the use of Veto Power to neutralize United Nations Security Council resolutions, and the new emerging issues, particularly global terrorism. The United Nations should be definite in application of its rules without special considerations to the interest of the permanent members of the security council. The security council should be reformed to accommodate interest of every ideological divide without any state or group determining its decision which will help to ensure equity in addressing global security concerns.